KEY CONCEPTS OF THE ERA IN THE MODERN UKRAINIAN SOCIO-POLITICAL LEXICON - Таран, Алла (Linguistic Bulletin (Movoznavchyi Visnyk), 2020)
The socio-political events in Ukraine at the beginning of the 21st century defined new realities and the notion in the conceptual picture of the Ukrainians world. The dramatic changes in the life of the community, the intense changes in the social and political life of Ukrainian society at the turn of the era, the change of generations, values, mental attitudes, the ever greater openness of Ukrainian society to globalization processes have found a natural reflection in the language, and have become the linguistic embodiment. Purpose – тhe characteristic of the key words today – witnesses of a new era of development of the Ukrainian society. Methods. According to research material in the scientific studies, the following methods are used: descriptive (linguistic techniques of observation and generalization), component analysis method (including analysis of dictionary definitions), method of contextual analysis and method of comparative analysis. Results. The object of study are the keywords which during the analyzed period showed the highest activity and had the most significant influence on the composition and functioning of the lexical system in the socio-political lexicon of Ukrainian society. The article explores the peculiarities of the words war, truce, corruption, freedom, and color tokens as particularly important symbols of certain political forces, in particular green. The paraphrases that have different pragmatic and stylistic potential, and therefore different performance in linguistic practice, are also analyzed. , but they do allow for the clarification and diversification of tokens verbalization. Originality. Explaining the trends in updating the socio-political vocabulary of the language and its resources and taking into account the diversity of linguistic tastes of the society, allows us to identify those concepts that have been the focus of social attention for some time. The systematic description of Ukrainian political metaphors is extremely important not only for generalizing this linguistic material, but also for determining its visibility for trends in the cognitive and communicative space of the modern Ukrainian. Conclusion. So understanding the capabilities and functions of high-relevance language tools for a community's consciousness during a particular period of its life is crucial.